Foot and Ankle Trauma Injuries Atlas of Surgical Procedures - Daghino, Walter (Springer International Publishing, 2018)
This full-color atlas offers a systematic guide to performing surgeries for the most common traumatic lesions of the foot and ankle. It features a wealth of didactic illustrations, achieved with a particular technique employing colors and transparencies that also reveals those anatomic structures that are not visible in the surgical field, but essential to a good outcome. Divided into seven chapters, the book provides coverage of all anatomic segments, presenting each topic logically and explaining all types of lesions, even the most difficult, complicated or infrequent ones; discussing the indications and objectives of the surgical treatment; describing the surgical technique (patient positioning, approach, tips and tricks for reduction, means of osteosynthesis); and providing recommended post-operative protocols. Unique in its exclusive focus on foot and ankle traumatology, this atlas offers an invaluable resource for all surgeons and residents who need a systematic overview of the main treatments options for these segments.